Pathological evaluation of massive left atrial calcification 35 years after mitral-aortic valve replacement. Issue 2 (February 2015) - Kawakami, Rika; Hao, Hiroyuki; Kimura, Naomi; Komatsu, Sei; Kodama, Kazuhisa; Hirota, Seiichi
Abstract Massive calcification of the left atrium is an uncommon complication of long-standing rheumatic valve disease, and is frequently revealed in patients with a previous operation on the mitral valve. An 84-year-old woman, who had a history of rheumatic valvulopathy and mitral-aortic valve replacement surgery 35 years previously, was admitted to our hospital due to congestive heart failure. Chest X-ray showed severe cardiomegaly with rim of calcification outlining the enlarged left atrium. Computed tomographic scan of the thorax clearly illustrated dense and partially thick plate-like calcification of left atrial free wall and interatrial septum. She died due to congestive heart failure 14 days after hospitalization and an autopsy was performed. Enlargement of left atrium with massive calcification was evident by gross pathology. Thick plate-like calcification with both erosion and mural hemorrhage was clearly shown by a cross-section of atrial wall. Organized and fresh fibrin thrombi were identified at the surface of left atrium. Calcified tissue penetrated into the wall of the left atrium and lack of myocardium underneath the massive calcified lesion was evident. Although rheumatic calcification of left atrium revealed by medical images was previously described, this is the first case report that demonstrates histopathological evaluation of massive atrial calcification. <Learning objective: Rheumatic calcification of entire left atrium after valve replacement surgery is known. Erosive calcification of the atrial wall with mural thrombi was identified by histology in this case. Old renal infarction was revealed by autopsy; therefore calcified atrium could be a source of distal embolism. Transmural calcification penetrated into the left atrial wall. We speculate on the difficulty in finding a cleavage plane for the endoatriectomy of massive calcified atrium in such a situation.>